COVID-19 and game park employees’ livelihoods in a distressed destination - Musavengane, Regis; Woyo, Erisher; Ndlovu, Agartha Olga (Routledge, 2022)
This paper examines the extent to which COVID-19 impacted the livelihoods of game park employees in a destination with ongoing political and economic challenges. Data were collected through interviewing employees revealed employee resilience levels and strategies to save their livelihoods during a crisis. It showcased the weaknesses of organizational social capital nodes in assisting employees during their vulnerable moments. It was found that employees on short-term contracts were the most affected, as they were the first to be laid off. The paper suggests up-skilling game park employees and develops empowerment interventions that help them generate second streams of income. This coping strategy is rarely discussed in the literature of tourism crisis and disaster management.